Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Multiliterasi di Sekolah Menengah Pertama Islam Terpadu Sahabat Al-Quran Binjai - Hairil Anwar; Rusyidi Ananda; Muhammad Rifa’i (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The aim of this research is to evaluate three main aspects: first, the suitability of Islamic Religious Education materials which apply a multiliteracy approach to improve student learning outcomes; second, ease of use of Islamic Religious Education materials with a multiliteracy approach in improving student learning outcomes; and third, the efficiency of Islamic Religious Education materials which utilize a multiliteracy approach to achieving student learning outcomes. This research was carried out at the Sahabat Qur'an Binjai IT Middle School during the first semester of the 2023-2024 academic year. The research method used is the development method using the Sugiyono model. The test subjects for this research were class VIII students, with a focus on developing multiliteracy-based PAI material. The resulting material has gone through a validation process by design experts, material experts and language experts, with an average validation result of 3.66 and a "very feasible" category. This product was also practically tested with an average result of 3.40 and the "practical" category. The research results show that multiliteracy-based PAI material has a high level of suitability for use in learning, based on expert assessment. This product has also proven to be practical in use. However, in terms of effectiveness, this material shows a moderate level of effectiveness in improving student learning outcomes, with statistical analysis showing tcount (4.26) which exceeds ttable (1.99) and N-Gain of 0.38 which is included in the "category" currently".